2010
DOI: 10.1007/s00198-009-1133-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and switching patterns among women with varied osteoporosis medication histories: 12-month results from POSSIBLE US™

Abstract: Baseline osteoporosis medication transitions were common in the first year of POSSIBLE US. Participants not on stable therapy at entry, or who reported severe side effects, or had poor physical health status were at higher risk for these transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
(19 reference statements)
1
22
1
Order By: Relevance
“…We therefore believe that side effects, and in particular, gastrointestinal tolerability may be an important contributing factor related to treatment persistence [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore believe that side effects, and in particular, gastrointestinal tolerability may be an important contributing factor related to treatment persistence [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Costeffectiveness studies based on clinical trial information have shown that treatment of osteoporosis is a cost-effective intervention for the patients with a risk of fracture defined in clinical trials and guidelines for intervention [8,53]. However, the adherence to therapy in clinical practice, both patient-reported and register-based, is much lower than in clinical trials [20,54]. This does not invariably change the cost-effectiveness of the intervention when compared with no treatment, since patients who drop out of treatment lose both costs and effects.…”
Section: Persistencementioning
confidence: 99%
“…Each participant was classified into one of five mutually exclusive treatment status cohorts using physician-reported medication history provided at study entry: new to therapy, stable on therapy, having recently switched therapy, having recently augmented therapy, or using calcium and/or vitamin D alone [21,22].…”
Section: Data Source and Study Populationmentioning
confidence: 99%